Heterogeneous Effects of the Cohesion Policy on Economic Growth in Poland: A Panel Data Analysis from 2007 to 2020 - Łukasz Robert Piętak (Ekonomista, 2025)
The aim of the study is twofold. Firstly, it examines the heterogeneous effects of Cohesion Policy on the growth of the NUTS 3 subregions of Poland. Secondly, it evaluates whether differences in Cohesion Policy outcomes are linked to the level of assistance. The econometric analysis spans the two planning periods of Cohesion Policy, covering 2007 to 2020. By using the dynamic Mean Group (DM) model, the study finds that Cohesion Policy produces a positive impact in 33 subregions (45%), an insignificant impact in 36 subregions (49%), and a negative impact in 4 subregions (5%). Furthermore, the econometric analysis finds that the effectiveness of EU policy is not determined solely by the assistance allocated to subregions. There are NUTS 3 units where a below-average influx of funds has yielded positive results, and others where a great deal of assistance has negatively affected economic performance. These results remain robust across various econometric approaches.